Proposal of Tayta Holistic Model with human development approach to improve the quality of life of older adults in Chachapoyas, Perú - Castro Silva, Jessica Yvonne (2023)
The existing panorama regarding the quality of life of the elderly in the district of Chachapoyas, Prior to the health context, there was a municipal Comprehensive Center for the elderly, where the elderly met periodically, the center carried out actions in favor of the protection and development of older adults. According to studies prior to the present, versions of social actors from the district of Chachapoyas, Amazonas; they make evident the situation of physical vulnerability, presence of emotional and psychological fragility with the consequent social displacement of the elderly. On the other hand, after carrying out the quality of life assessment of the elderly, it was found that they presented a regular level of quality of life. Therefore, the objective of this study was to formulate a model proposal with a human development approach to improve the quality of life of older adults in the Chachapoyas district. In its structure, 7 fundamental pillars are considered with a motivational, holistic approach that allows strengthening the well-being of the elderly.